2012
DOI: 10.1590/s0365-05962012000200010
|View full text |Cite
|
Sign up to set email alerts
|

NAPSI utilization as an evaluation method of nail psoriasis in patients using acitretin

Abstract: The method was easy and of rapid execution while potentially bringing information about changes in nail plate and matrix during treatment. The Nail Psoriasis Severity Index does not quantify the existing lesions and might not have the sensitivity to detect small changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 10 publications
(4 reference statements)
0
11
0
2
Order By: Relevance
“…43 Conversely, a Brazilian study conducted on 20 patients found no significant improvements after a four-month treatment course. 44 However, it is important to note that acitretin may cause adverse effects such as nail thinning, which may impact areas of the nail plate which have normal thickness. 8 …”
Section: Treatmentmentioning
confidence: 99%
“…43 Conversely, a Brazilian study conducted on 20 patients found no significant improvements after a four-month treatment course. 44 However, it is important to note that acitretin may cause adverse effects such as nail thinning, which may impact areas of the nail plate which have normal thickness. 8 …”
Section: Treatmentmentioning
confidence: 99%
“…Improvement was measured using the Nail Psoriasis Severity Index (NAPSI) score and the modified NAPSI score. The NAPSI score, proved to be an effective tool in quantifying changes in the nail, evaluates the presence or absence of lesions such as salmon patches, onycholysis, nail bed hyperkeratosis, pitting, leukonychia, and crumbling . The modified NAPSI score is a measure of severity of nail matrix and nail bed psoriasis on each nail quadrant.…”
Section: Effectivenessmentioning
confidence: 99%
“…NAPSI scoring system has some limitations, as it does not specifically consider the severity of nail matrix or nail bed involvement. In a recent report by Mukai et al [14], NAPSI scores were evaluated in psoriatic patients using acitretin, and it was concluded that the method was easy and rapid in measuring the improvement of the treatment; however, it did not quantify the existing lesions and might not detect small changes. In 2007, a modified NAPSI (mNAPSI) was proposed by Cassell et al [15] in order to increase the sensitivity of NAPSI, using a qualitative gradation of severity for each parameter from 0 to 3 in each quadrant.…”
Section: Introductionmentioning
confidence: 99%